O tratamento penal do uso indevido de informação privilegiada no mercado de capitais insider trading - Santana, Melina Marques Mendes (2012)
This work aims at assessing the criminal treatment of the insider trading activities on the capital markets. It begins by assessing the most relevant aspects of capital markets and their impact for the economy. Subsequently, it studies the value of the information and the way it should be dealt with by current and potential market participants and any other stakeholder. Following the information collection phase, the differences between white collar crimes and conventional crimes are scrutinized. Then, the work is performed by verifyingand describing how the insider trading has been defined as a crime in the Brazilian legal system and by pointing out the pros and cons of the current legislation. There is also a brief analysis of the international legislation linked to the subject. Ultimately, this work intends to contribute to the elucidation of the insider trading subject and to the unequivocal elimination of that practice